Renin-Angiotensin System-Growth Factor Cross-Talk: a Novel Mechanism for Ureteric Bud Morphogenesis - Yosypiv, Ihor V. (2008)
The renin-angiotensin system (RAS) plays a critical role in kidney development. Mutations in the genes encoding components of the RAS cause a spectrum of congenital abnormalities of the kidney and renal collecting system ranging from hypoplasia of the renal medulla and hydronephrosis in mice to renal tubular dysgenesis in humans. However, the mechanisms by which an intact RAS controls proper renal system development and how aberrations in the RAS result in abnormal kidney and renal collecting system development are poorly understood. The renal collecting system originates from the ureteric bud (UB). A number of transcription and growth factors regulate UB branching morphogenesis to ultimately form the ureter, pelvis, calyces, medullary and cortical collecting ducts. Importantly, UB morphogenesis is a key developmental process that controls organogenesis of the entire metanephros. This review emphasizes emerging insights into the role for the RAS in UB morphogenesis and explores the mechanisms whereby RAS regulates this important process. A conceptual framework derived from recent work indicates that cooperation of angiotensin II AT(1) receptor and receptor tyrosine kinase signaling performs essential functions during renal collecting system development via control of UB branching morphogenesis.